What Effects Have Resident Work‐hour Changes Had on Education, Quality of Life, and Safety? A Systematic Review. Issue 5 (May 2015) - Harris, Joshua D.; Staheli, Greg; LeClere, Lance; Andersone, Diana; McCormick, Frank
Abstract: Background: More than 15 years ago, the Institute of Medicine (IOM) identified medical error as a problem worthy of greater attention; in the wake of the IOM report, numerous changes were made to regulations to limit residents' duty hours. However, the effect of resident work‐hour changes remains controversial within the field of orthopaedics. Questions/purposes: We performed a systematic review to determine whether work‐hour restrictions have measurably influenced quality‐of‐life measures, operative and technical skill development, resident surgical education, patient care outcomes (including mortality, morbidity, adverse events, sentinel events, complications), and surgeon and resident attitudes (such as perceived effect on learning and training experiences, personal benefit, direct clinical experience, clinical preparedness). Methods: We performed a systematic review of PubMed, Scopus, CINAHL (Cumulative Index to Nursing and Allied Health Literature), and Google Scholar using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) guidelines. Inclusion criteria were any English language peer‐reviewed articles that analyzed the effect(s) of orthopaedic surgery resident work‐hour restrictions on patient safety, resident education, resident/surgeon quality of life, resident technical operative skill development, and resident surgeon attitudes toward work‐hour restrictions. Eleven studies met study inclusion criteria. One study was a prospective analysis, whereas 10 studies were of level IV evidence (review of surgical case logs) or survey results. Results: Within our identified studies, there was some support for improved resident quality of life, improved resident sleep and less fatigue, a perceived negative impact on surgical operative and technical skill, and conflicting evidence on the topic of resident education, patient outcomes, and variable attitudes toward the work‐hour changes. Conclusions: There is a paucity of high‐level or clear evidence evaluating the effect of the changes to resident work hours. Future research in this area should focus on objective measures that include patient safety as a primary outcome.